Urban Sprawl Negative Impact: Enkomi Return Phase - KAMYAR FULADLU (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
Most of the cities around the world are dealing with different kinds of problems such as social, environmental, economic and others. However, for many years, urban planners have attempted to find solutions that fit within the context and have put them into practice in order to shape the form of a city accordingly. One of the controversial problems which most of the developing and developed countries deal with it is urban sprawl, which affects everything and everyone in different scales. In T.R.N. Cyprus urban sprawl didn’t promote auto-dependency. Despite urban sprawl in T.R.N. Cyprus have many repercussions, one of the important impacts which are considered in this articles are the psychological impact of urban sprawl, also this article attempt to divide urban sprawl leaving condition into three phases, and promote the contemplate phase which makes sprawl inhabitants think and return to the inner-city neighbourhood again.